Serbian and Albanian toponyms of the village Oslare near Bujanovac - Jašović, Golub M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper deals with the toponymy of the Oslare village. Oslare is located just five kilometers south of Bujanovac. The settlement has been founded on the left bank of the Moravica River, that is, on the western side of the Belgrade – Skoplje highway and on the very border of Vranjsko Pomoravlje and Presevo Moravica. The village residents are of Serbian and Albanian origins. Some of the Serbs are locals and some migrated to Oslare from Kosovsko Pomoravlje as well as from the nearby villages. Albanians migrated to Oslare from Albania and other areas. Among Albanian residents are also Serbs who took Islam. Most of them took the name Taci but there are other families as well. The main concern of this paper is the recording of the Oslare toponymy. This is achieved through conversation with both Serbian and Albanian residents in both Serbian and Albanian languages. We have also analyzed semantics of the collected toponymes and their function in the everyday use. We tried to compare toponymes used by Serbs, who speak Serbian language (southmoravian dialect) and Albanians, both of those who are of Serbian origins and of those who migrated from Albania.